Characterization of pre-existing anti-PEG and anti-AGAL antibodies towards PRX-102 in patients with Fabry disease - Lenders, Malte; Feidicker, Lina Marleen; Brand, Stefan-Martin; Brand, Eva (Frontiers in Immunology, 2023)
Polyethylene glycol (PEG)ylated drugs are used for medical treatment, since PEGylation either decreases drug clearance or/and shields the protein from undesirable immunogenicity. PEGylation was implemented in a new enzyme replacement therapy for Fabry disease (FD), pegunigalsidase-alfa (PRX-102). However, exposure to PEG via life-style products and vaccination can result in the formation of anti-PEG antibodies. We demonstrate the de novo formation of functional anti-PEG antibodies in a healthy male after the second mRNA-based vaccination against SARS-CoV-2. Consequently, we analyzed the frequency and inhibitory function of anti-PEG and anti-α-Galactosidase A (AGAL) antibodies in 102 FD patients (46.9% males). We identified 29 out of 87 (33.3%) patients with low anti-PEG titers. Sera from patients without anti-AGAL antibodies [n=70] showed a higher rescued AGAL activity of agalsidase-beta and PRX-102 [both p<0.0001] compared to those with anti-AGAL antibodies [n=15]. Sera from anti-AGAL antibody-negative and -positive patients had less inhibitory effects on PRX-102 (rescued activity: 89±6% versus 85±7% and 49±26% versus 25±32%; both p<0.0001). Enzyme stability assays demonstrated that AUCs in anti-AGAL-negative sera (n=20) were 7.6-fold higher for PRX-102, while AUCs of both enzymes in anti-AGAL-positive sera (n=6) were decreased. However, AUC for PRX-102 was 33% of non-anti-AGAL-positive sera treated PRX-102 and 5-fold higher compared to agalsidase-beta. Anti-PEG antibodies had no significant effects on serum half-life of PRX-102, probably due to low titers. Conceivably, therapy efficacy may be superior under next-generation PRX-102 therapy compared to current enzyme replacement therapies in terms of reduced inhibitory effects of anti-AGAL and minor inhibitory effects of anti-PEG antibodies.